Village Governance in Integrating Conservation Policies: Insights from Bangka Belitung - Abduh, Muhammad; Religia, Pijar (Universitas Teuku Umar, 2026)
This study investigates the role of village governance as a key driver for Environmental Conservation Efforts (ECE), with a focus on resource-dependent regions like Bangka Belitung Province. Data from the 2021 Indonesian Village Potential Census (Podes) identified 34 variables related to governance, village assets, and environmental policies. Using bivariate analysis and logistic regression, the research finds that inter-village cooperation, village financial systems, and governance mechanisms are strongly associated with successful ECE outcomes. Specifically, inter-village cooperation was found to increase the likelihood of engaging in conservation activities (AOR: 3.26; 95% CI: 1.47–7.24). However, challenges such as the limited use of open public spaces and insufficient policy integration were also identified. The study underscores the importance of robust governance frameworks in fostering sustainable environmental practices and mitigating such challenges. Despite the limitations of cross-sectional data, this research provides valuable insights for policymakers, emphasizing the need for integrated governance and community-based initiatives to improve conservation efforts. These findings offer a replicable model for environmental conservation strategies in regions under pressure from resource exploitation.